Hattat Mehmed Rıza Bey - Akçay, Sement (My University, 2019)
Hattat Mehmed Rıza Bey, Türk ta’lik mektebinin oluşum süreci hattatlarındandır.Mehmed Rıza Bey, H. 1249 [1835] yılında İstanbul’da doğmuştur. Babası Mehmed Ataullah Bey Anadolu Kadıaskerliği payelilerindendir. İlmiye sınıfına mensup diğer ailelerin çocuklarında olduğu gibi erken yaşlarda özel hocalardan ders alarak eğitimi başlamış olmalıdır. Mehmed Rıza Bey, erken yaşlardan itibaren İstanbul’un çeşitli medreselerinde müderrislik, yirmi üç yaşından itibaren de İmparatorluğun farklı yerlerinde naiplik ve kadılık görevlerinde bulunmuştur. Mehmed Rıza Bey’in son görevi İstanbul kadılığıdır. İstanbul kadılığı sonrası mazuliyeti esnasında, 13 Ş 1313 [29 Ocak 1896]’da İstanbul’davefat etmiştir. Hat sanatı tarihi ve hattat biyografileri ile ilgili eserlerde Mehmed Rıza Bey ilgili bilgiler birkaç paragrafı geçmeyecek şekildedir. Mezkür eserlerdeki bilgiler birbirinin tekrarı hükmündedir. Aynı zamanda Mehmed Rıza Bey’in yayınlanmış eserleri de iki elin parmağını geçmeyecek kadar azdır. Var olan bilgilerden yola çıkarak ne Mehmed Rıza Bey’in hayatı hakkında sağlıklı bir bilgiye; ne de bilinen eserlerinden yola çıkarak Mehmed Rıza Bey’in sanatı hakkında yeterli bir kanıya ulaşmak mümkün gözükmemektedir.Biz bu çalışmamızda, Meşihat arşivinden, Ruznamçe defterlerinden, Tarik defterlerinden, Başbakanlık Osmanlı arşivinden yararlanarak Mehmed Rıza Bey’in kronolojisini ortaya çıkarmaya çalıştık. Mehmed Rıza Bey’in elli iki eserini de çalışmamıza konu ettik. Böylece Mehmed Rıza Bey’in sanatı hakkında daha sağlıklı kanılara ulaşılmasının önünü, bir nebze de olsa açmaya çalıştık. Mehmed Rıza Bey ile ilgili çalışmamızın neticesinde kısaca şunları söyleyebiliriz: Mehmed Rıza Bey’in yaşadığı, eser verdiği dönem Türk ta’lik ekolünün henüz oluştuğu bir dönemdir. Mehmed Rıza Bey’in bürokrat – sanatkar oluşu sanatının önünde bir mania teşkil etmiş ve yine görevleri nedeniyle İstanbul’dan (sanat çevrelerinden) uzakta oluşu sanatkarlığını olumsuz yönde etkilemiştir.

Calligrapher Mehmet Rıza Bey is one of the calligraphers in the formation process of Turkish ta’lik school.Mehmed Rıza Bey was born in İstanbul in 1249 (Arabic hegira calendar) [AD / 1835]. His father Mehmed Ataullah Bey was one of the anatolian military officer (kadi-ul asker) He started his education by taking private tutors from early ages as seen in the children of other families which are members of the Ilmiye class (Ottoman ulama).He started to work as mudarris in the madrasah of İstanbul at early ages From twenty three years of age upward, he continued to his career as regent and kadi (Muslim judge) in different places of the Ottoman Empire. The last appointment of Mehmed Rıza Bey was kadi authority of İstanbul. After this mission was completed, he died in İstanbul during the process of dismission from his job. 13 Ş 1313 [29th January 1896].In the works related to the history of calligraphy and calligraphers’ biographies, the information related to Mehmed Rıza Bey doesn’t exceed a few paragraphs. The above mentioned works include repeated information. At the same time, the works of Mehmed Rıza Bey can be counted on the fingers of hands.Based on the existing information and written works, it seems that it is not possible to reach a sufficient opinion about the life and art of Mehmed Rıza Bey.In this study, the chronology of Mehmed Rıza Bey is explored by taking advantage of the Meşihat archives, Ruznamçe notebooks, Tarik books and Ottoman archives.We mentioned about fifty works of him in this paper. In this way, we have paved the way for a better understanding of the art of Mehmed Rıza Bey.As a result of our work with Mehmed Rıza Bey, we can say briefly: The period in which Mehmed Rıza was living and performing his art was a period in which Turkish Ta’lik School was newly formed. Mehmed Rıza Bey's position as a bureaucratist and artist entailed a hindrance on his art. Also, his being away from Istanbul (art groups)due to his duties negatively affected his profession as a calligrapher. Calligrapher Mehmet Rıza Bey is one of the calligraphers in the formation process of Turkish ta’lik school.Mehmed Rıza Bey was born in İstanbul in 1249 (Arabic hegira calendar) [AD / 1835]. His father Mehmed Ataullah Bey was one of the anatolian military officer (kadi-ul asker) He started his education by taking private tutors from early ages as seen in the children of other families which are members of the Ilmiye class (Ottoman ulama).He started to work as mudarris in the madrasah of İstanbul at early ages From twenty three years of age upward, he continued to his career as regent and kadi (Muslim judge) in different places of the Ottoman Empire. The last appointment of Mehmed Rıza Bey was kadi authority of İstanbul. After this mission was completed, he died in İstanbul during the process of dismission from his job. 13 Ş 1313 [29th January 1896].In the works related to the history of calligraphy and calligraphers’ biographies, the information related to Mehmed Rıza Bey doesn’t exceed a few paragraphs. The above mentioned works include repeated information. At the same time, the works of Mehmed Rıza Bey can be counted on the fingers of hands.Based on the existing information and written works, it seems that it is not possible to reach a sufficient opinion about the life and art of Mehmed Rıza Bey.In this study, the chronology of Mehmed Rıza Bey is explored by taking advantage of the Meşihat archives, Ruznamçe notebooks, Tarik books and Ottoman archives.We mentioned about fifty works of him in this paper. In this way, we have paved the way for a better understanding of the art of Mehmed Rıza Bey.As a result of our work with Mehmed Rıza Bey, we can say briefly: The period in which Mehmed Rıza was living and performing his art was a period in which Turkish Ta’lik School was newly formed. Mehmed Rıza Bey's position as a bureaucratist and artist entailed a hindrance on his art. Also, his being away from Istanbul (art groups)due to his duties negatively affected his profession as a calligrapher. Calligrapher Mehmet Rıza Bey is one of the calligraphers in the formation process of Turkish ta’lik school.Mehmed Rıza Bey was born in İstanbul in 1249 (Arabic hegira calendar) [AD / 1835]. His father Mehmed Ataullah Bey was one of the anatolian military officer (kadi-ul asker) He started his education by taking private tutors from early ages as seen in the children of other families which are members of the Ilmiye class (Ottoman ulama).He started to work as mudarris in the madrasah of İstanbul at early ages From twenty three years of age upward, he continued to his career as regent and kadi (Muslim judge) in different places of the Ottoman Empire. The last appointment of Mehmed Rıza Bey was kadi authority of İstanbul. After this mission was completed, he died in İstanbul during the process of dismission from his job. 13 Ş 1313 [29th January 1896].In the works related to the history of calligraphy and calligraphers’ biographies, the information related to Mehmed Rıza Bey doesn’t exceed a few paragraphs. The above mentioned works include repeated information. At the same time, the works of Mehmed Rıza Bey can be counted on the fingers of hands.Based on the existing information and written works, it seems that it is not possible to reach a sufficient opinion about the life and art of Mehmed Rıza Bey.In this study, the chronology of Mehmed Rıza Bey is explored by taking advantage of the Meşihat archives, Ruznamçe notebooks, Tarik books and Ottoman archives.We mentioned about fifty works of him in this paper. In this way, we have paved the way for a better understanding of the art of Mehmed Rıza Bey.As a result of our work with Mehmed Rıza Bey, we can say briefly: The period in which Mehmed Rıza was living and performing his art was a period in which Turkish Ta’lik School was newly formed. Mehmed Rıza Bey's position as a bureaucratist and artist entailed a hindrance on his art. Also, his being away from Istanbul (art groups)due to his duties negatively affected his profession as a calligrapher.
Keywords: Calligraphers, Turkish; Calligraphy; Hat Sanatı; Hattat Mehmed Rıza Bey; Hattat Mehmed Rıza Bey, 1835-1896; Hattatlar, Türk; History; Islam; İslamiyet; Nesta’lik; Ta’lik; Tarih; Turkish Ta’lik School; Türk Ta’lik Mektebi; Yesarizade Mustafa İzzet Efendi; Yesarizade Mustafa İzzet Efendi Hattat Mehmed Rıza Bey